2020
DOI: 10.4314/acsj.v28i1.22s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of entrepreneurship education on Egerton University’s graduates’ intention to start a business

Abstract: Entrepreneurship training has been introduced in most Higher Education Institutions (HEI) in sub-Saharan Africa countries to enhance graduate self-employment. The purpose of this study was to examine the impact of entrepreneurship training on Egerton University’s graduates’ intention to start a business. This study used the Ajzen’s theory of planned behaviour (TPB) in a cross sectional survey, conducted during April to May, 2016. A sample of 341 business and non-business Egerton University graduates, enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…e regression equation was statistically tested by ANOVA: model 1 was regression, with a degree of freedom � 5, SS regression � 20.546, and Ms regression � 4.109; and residual residual, degree of freedom � 953, SS residual � 586.034, and Ms residual � 0.615; the F value is 6.682, and the P value is < 0.000, which indicates that the regression equation is meaningful [23]. Model 2 was regression with a degree of freedom � 13, SS regression � 266.838, and Ms regression � 20.526; and residual residual, degree of freedom 945, SS residual � 339.742, and Ms residual � 0.360; the F value is 57.093, and the P value is < 0.000, which indicates that the regression equation is meaningful.…”
Section: Regression Analysis Of Entrepreneurial Competencementioning
confidence: 99%
“…e regression equation was statistically tested by ANOVA: model 1 was regression, with a degree of freedom � 5, SS regression � 20.546, and Ms regression � 4.109; and residual residual, degree of freedom � 953, SS residual � 586.034, and Ms residual � 0.615; the F value is 6.682, and the P value is < 0.000, which indicates that the regression equation is meaningful [23]. Model 2 was regression with a degree of freedom � 13, SS regression � 266.838, and Ms regression � 20.526; and residual residual, degree of freedom 945, SS residual � 339.742, and Ms residual � 0.360; the F value is 57.093, and the P value is < 0.000, which indicates that the regression equation is meaningful.…”
Section: Regression Analysis Of Entrepreneurial Competencementioning
confidence: 99%
“…Capatina et al (2023) reported the prominent role of technological transfer from universities and research centres to the business incubation process. Mshenga et al (2020) found that graduates' intention to launch a business is most strongly predicted by their optimistic attitude. The next most important factors are responsiveness, risk-taking, and self-motivation.…”
Section: Enablers Of Students' Intentionsmentioning
confidence: 99%
“…Mshenga et al . (2020) found that graduates' intention to launch a business is most strongly predicted by their optimistic attitude.…”
Section: Students' Entrepreneurial Intentions: a Literature Reviewmentioning
confidence: 99%